2017
DOI: 10.1016/j.scitotenv.2016.10.229
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metallic engineered nanoparticles upon plant systems: An analytic examination of scientific evidence

Abstract: Recent evidence for the effects of metallic engineered nanoparticles (ENPs) on plants and plant systems was examined together with its implications for other constituents of the Society-Environment-Economy (SEE) system. In this study, we were particularly interested to determine whether or not metallic ENPs have both stimulatory and inhibitory effects upon plant performance. An emphasis was made to analyze the scientific evidence on investigations examining both types of effects in the same studies. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…It has been reported that nanotechnology may improve the production of the crop with the development of nano-fertilizers and nano-treatments for plant diseases. [6][7][8] Different nanoparticles (NPs) have been studied for the treatment of plant diseases. 9 Particularly, it has been claimed that copper (Cu) NPs can be a potent fungicide.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nanotechnology may improve the production of the crop with the development of nano-fertilizers and nano-treatments for plant diseases. [6][7][8] Different nanoparticles (NPs) have been studied for the treatment of plant diseases. 9 Particularly, it has been claimed that copper (Cu) NPs can be a potent fungicide.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of nanotechnology and increased inclusion of nanoscale (1-100 nanometer in size) components in various products have included the use of nanoparticles of micronutrients as fertilizers and agropesticides. Recent reviews in this area describe both the negative and positive aspects of nanoparticle nutrients on plant growth and productivity [8][9][10][11][12]. Notably, because nanoparticles are more reactive than their bulk-scale equivalents, these materials may cause greater toxicity or beneficial effects on agricultural crops.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature contains very few studies that are focused on nano-Mn behavior in plant systems, particularly when compared to the number of reports on nano-ZnO, nano-CuO, or nano FeO [9][10][11]14]. The few published studies show that nano Mn treatment resulted in an increase in mung bean growth, 52% and 38%, for root and shoot [3]; a 22% increase in eggplant yield [15]; non-significant effects on root elongation of White Mustard [16]; no effect on lettuce germination, but a dose-dependent increase in plant root length [17]; and, suppression of disease progression over time in watermelon that was not accompanied by significant yield increase [18].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing interest in nanotechnology and nanotechnology applications, the relationships and behaviour of nanoparticles in the environment and their relationship to plant organisms have been summarized by various authors [33,69,70,71]. Nanoparticles enter the environment naturally or through an engineering approach [72].…”
Section: Resultsmentioning
confidence: 99%
“…Plants can absorb nanoparticles by all exposure routes including soil, water, and air [32]. An important aspect is the risk assessment of nanoparticles and the understanding of nanoparticle interactions with plants as essential components of all ecosystems [33,34]. Application of nanoparticles to a plant can result in the modification of gene expression and alteration of genetic pathways, which ultimately affects the growth and development of that plant [35].…”
Section: Introductionmentioning
confidence: 99%